Penguatan Kapasitas Petani Melalui Penyuluhan Studi Pada (Balai Penyuluhan Pertanian) BPP Kecamatan Sukorejo Kabupaten Ponorogo - Fitriani, Intan Fransisca; Ridho, Irvan Nur; Triono, Bambang; Hilman, Yusuf Adam (JURNAL DINAMIKA, 2024)
Agriculture is one of the most important sectors for Indonesia's economy. The role of agricultural extension as a facilitator, motivator, and supporter of farmers' activities is central in providing guidance to farmers regarding sustainable and environmentally friendly farm management. Research to understand the strengthening of farmers' capacity through agricultural extension was conducted in a study at the Agricultural Extension Center (Balai Penyuluhan Pertanian or BPP) in Sukorejo District, Ponorogo Regency. Data collection involved observation, interviews, and documentation, with data analysis using the processes of data collection, data reduction, data presentation, and conclusion drawing. The BPP of Sukorejo District has shown a strong commitment to implementing agricultural extension programs with a focus on efficiency and effectiveness. Through regular monitoring and evaluation, the BPP ensures optimal use of budgets and resources and applies systematic data collection and analysis to identify areas for improvement and implement feedback from farmers and other stakeholders. Strategies such as detailed planning, rigorous evaluation, and the use of effective technology and communication methods enable the BPP to achieve maximum results with minimal costs while maintaining high-quality extension services. The Farmers' Group Association (Gapoktan) also plays a crucial role in ensuring the program's success through active monitoring, evaluation, and feedback collection, as well as conducting regular evaluation meetings with the BPP to assess the progress and effectiveness of the extension services objectively. The close collaboration between the BPP and Gapoktan in various aspects of the extension program, including monitoring, evaluation, and information dissemination, demonstrates that a comprehensive and inclusive approach can enhance transparency, accountability, and program effectiveness. With the active involvement of the farming community in every stage of planning and implementation.